RECOMMENDATIONS FOR THE IMPROVEMENT OF THE CONSERVATION TECHNOLOGY OF SPRING CEREALS IN THE TRANSYLVANIAN PLATEAU - Teodor Rusu; Felicia Chețan; Ileana Bogdan; Paula Ioana Moraru; Adrian Ioan Pop; Camelia Alămorean (Agricultura)
In the hilly area of the Transylvanian Plateau, due to the non-application of specific cultivation technologies, the failure to comply with the requirements to combat limiting phenomena and factors, in particular soil erosion, coupled on the other hand with the lack of means of production, the non-existence of technologically adequate agricultural machinery systems, but also insufficient in terms of quantity, modest levels of production have been obtained in recent years. The evolution of soils in the Transylvanian Plateau is influenced by a combination of natural and anthropogenic factors. The natural factors are climate - in particular precipitation, wind, drought and relief. The soil is vulnerable to the climate because heavy rainfall washes away the soil, causing it to lose its fertile qualities; anything washed away by rainfall affects lakes, settlements and communication routes. The list of anthropogenic factors is longer and includes: inappropriate agricultural technologies, urban aggression and the social component, which includes an ageing population, lack of interest in the countryside among young people, low prices for agricultural products, lack of infrastructure and deforestation. The specific conditions of the Transylvanian Plateau make it necessary for spring cereals to opt for varieties that are well adapted to the specific climate, characterized by relatively short and cool summers and cold springs. Varieties with resistance to foliar diseases and drought conditions are recommended as they can reduce yield losses. Varieties that ensure harvest before the onset of summer drought are preferred. Direct seeding allows spring cereals to be sown without disturbing the topsoil. This reduces soil compaction and helps maintain moisture. Conservation tillage is a viable solution for growing spring cereals with a positive impact on the soil and the environment. It can contribute significantly to a more sustainable farming system, conserving natural resources and reducing long-term production costs. Adapting farmers to these methods can bring considerable long-term economic and environmental benefits.